PENGENALAN AI DAN COMPUTER VISION UNTUK SISWA SMK RAFLESIA DEPOK - Aktavia, Widodo; Ade Nuryana (JAMAIKA: JURNAL ABDI MASYARAKAT, 2026)
This community service activity aims to improve digital literacy and understanding of artificial intelligence technology among vocational high school students, particularly those majoring in Software and Game Development (PPLG). The rapid growth of Artificial Intelligence (AI) and Computer Vision requires vocational students not only to become technology users but also to understand the concepts, working processes, and potential applications in industry. The activity was conducted at SMK Raflesia Depok on November 13 with 20 participants from the 12th-grade PPLG class. The program employed interactive lectures, hands-on demonstrations, an introduction to how Computer Vision works, and practical sessions using Google Teachable Machine to train image-based classification models without programming. The results show that students significantly improved their understanding of AI fundamentals, the workflow of Computer Vision, and its use in modern applications such as face recognition, augmented reality, and object detection. In addition, students were able to create simple classification models using images captured in real time. This activity had a positive impact on increasing student interest in AI and provided foundational knowledge aligned with the competency needs of the digital industry.